Oiketicus kirbyi (Guilding, 1827) (Lepidoptera: Psychidae): first record feeding on Malus domestica Borkh. (Rosaceae) in Brazil - Pinheiro, Rodrigo A.; Santos, Samuel V.; Silva, Luana G.; Silvério, Poliana P.; Oliveira-Júnior, Gilson G. S.; Assis-Júnior, Sebastião L.; Soares, Marcus A. (Entomological Communications, 2025)
Several phytophagous insects, such as sap-suckers, borers, and defoliators, affect apple (Malus domestica Borkh. (Rosaceae)) production in Brazil. Recording insects that cause damage to plants can facilitate their identification when making control decisions. Given the importance of apple production in Brazil, it was necessary to report the occurrence of Oiketicus kirbyi (Guilding, 1827) (Lepidoptera: Psychidae) feeding on M. domestica leaves in Brazil. The caterpillars identified as O. kirbyi were observed damaging leaves of the leaves of M. domestica. These were collected, determined, and deposited in an entomological reference collection, constituting the first record of the species feeding on M. domestica in Brazil.